Ice challenge in recent summer Olympic Games - Racinais, S.; Ihsan, M.; Grant, M.-E.; Dablainville, V.; Rousse, Y.; Schobersberger, W.; Budgett, R.; Engebretsen, L. (British Journal of Sports Medicine, 2024)
From injury and illness management to recovery, cryotherapy is commonly used by athletes and their support personnel. And the simplest version of this remains the application of ice. However, the use of ice is not trivial, nor should it be taken for granted. Apart from logistical challenges related to production, transportation and storage, ice is often used to obtain benefits which are not evidence-based. More importantly, ice could have the opposite effect to that expected such as delayed tissue regeneration or impaired recovery. This editorial discusses recent trends in ice usage and resource requirements at the Olympic Games within the context of an uncertain evidence base for the clinical application of cryotherapy.